Improving the Quality of Student Memorizing Using the Wafa Method in Elementary Schools: Peningkatan Kualitas Hafalan Siswa Menggunakan Metode Wafa di Sekolah Dasar - Hidayat, Laksmana Safaq; Romadlon, Dzulfikar Akbar (Indonesian Journal of Innovation Studies, 2022)
The Wafa method is one of the methods used to memorize the Qur'an by maximizing the right brain. This method has the characteristics of reading the Koran with hijaz rhythm, learning with sound equations, as well as syllable grouping, and in this wafa method using movements according to the translation of the verse. The purpose of this study is to determine the application of the success of the wafa method in improving the memorization of students and to determine the success of the wafa method in improving the memorization of students at the Integrated Islamic Elementary School Nurul Fikri Sidoarjo. This study uses qualitative research using a phenomenological approach. The subjects in this study were the coordinator of the Qur'anic teacher and the Qur'an tahfidz team. The types of data sources obtained are primary and secondary data sources. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used in this study are data reduction, data condensation, data presentation and data verification. The results of this study found that in the process of learning the Qur'an and Tahfidz at the Integrated Islamic Elementary School Nurul Fikri Sidoarjo applied the Wafa method using the TANDUR strategy (Grow, Natural, Peaceful, Demonstration, Repeat and Celebrate) which was packaged in five stages (opening practice, teaching , assessment and closing). In the aspect of Tahfidz, it uses Hijaz rhythm with ascending, medium, and low scales. With the use of strategies from the 5P concept as seen from the acquisition of students' memorization of the Koran, it can be said that the application of the Wafa method in improving students' memorization and the success of the wafa method in improving memorization can be said to run very well and effectively because considering that most students already have the option to complete memorization of the specified juz and able to achieve more than the targeted memorization.